The Religiosity in Gouverneurs de la Rosee by Jacques Roumain: Between the Immobility and the Redemption - Hurtado-Ruiz, P (UNIV ATLANTICO, FAC CIENCIAS HUMANAS, 2017)
This paper analyzes the religiosity in the novel Gouverneurs de la rosee by the Haitian writer Jacques Roumain. For that purpose, it states that the religion professed by the character is a syncretism between the Catholicism and the voodoo, in which the conflict between the divinity imposed in the slavery period and the divinities inherit from Africa is manifested. This study analyzes the position of immobility that this religiosity means to the people of Fonds-Rouge, in opposition to the Marxist vision of the work introduced by Manuel, the principal character in the novel. Finally, despite the criticism to the religion, the fate imposed by the voodoo divinities is inexorably fulfilled, in contraposition to the catholicism, which is questioned because it is a white s religion.